Upgrading in design scheme of terminal jetty for Majlis Perbandaran Manjung at Jalan Titi Panjang, 32100, Lumut Perak / Faizullomi Arif - Arif, Faizullomi (Faculty of Architecture, Planning and Surveying, 2011)
This final report is compulsory for obtaining a Diploma in Interior Design, Universiti Teknologi Mara. This course is a comprehensive act as a design understanding exercise for the students, where at this level the students are given to prepare a design scheme based on analysis and observations related to issues and problems that they encounter while dealing with the design process. This final report writing is a report for final project Diploma in Interior Architecture on ‘Proposed New Design of Sarawak Handicraft Gallery at Old Court House, Gambier road, 93050 Kuching Sarawak. The purpose of this project is to promote the handicraft of Sarawak and to attract tourists. The main purpose of this research is to introduce the craft history or myth and the function uses Sarawak handicraft. With this new approach, it can give a new knowledge for tourist about the relationship between crafts and human in Sarawak at the past. The research method used in this project based observation another gallery in Malaysia only reforms for the facilities and comfort visitors. Traditional elements to be used as a metaphor that is often less pronounced and can not get concern among visitors. As a place information and innovative on innovative which focus the art of crafts are appropriate for the information center should be free thinking of the way to make the interest of visitors to come our gallery. Therefore, a good planning have been made to design a new Sarawak Handicraft gallery with applying new technologies system and new display system. Hopefully this design can give benefits to visitors.